Dual function of Desmidorchis retrospiciens-derived gold nanoparticles as antibacterial and osteoinductive agent for treating osteomyelitis - Abdallah, Basem M.; Rajendran, Peramaiyan; Ali, Enas M. (Frontiers in Microbiology, 2025)
IntroductionOsteomyelitis is a chronic inflammation of bone due to pathogenic infection mainly by methicillin-resistant Staphylococcus aureus (MRSA). Osteomyelitis can cause severe bone damage and pathologic fractures, which subsequently result in a high physical disability rate. Thus, a therapeutic agent with antibacterial and bone regenerative activities can be effective for managing osteomyelitis.MethodsWe phyto-fabricated gold nanoparticles using plant extract from Desmidorchis retrospiciens (DR-AuNPs) and examined their antibacterial and osteoinductive activities. The biosynthesis of DR-AuNPs was confirmed with several characterization techniques, including scanning and transmission electron microscopy, X-ray diffraction (XRD), energy-dispersive X-ray analysis (EDX), and Fourier transform infrared spectroscopy (FTIR). Biofilm assays and reactive oxygen species (ROS) analysis were used to examine the antibacterial effect of DR-AuNPs. In vitro and ex vivo cell biology assays were used to study the osteoinductive effect of DR-AuNPs.ResultsDR-AuNPs displayed substantial antibacterial activity against MRSA-induced osteomyelitis by increasing ROS production, membrane leakage, membrane permeability, and disruption of surface structure in the MRSA. Several anti-biofilm assays and electron microscopic studies have demonstrated the efficacy of DR-AuNPs in significantly inhibiting the formation of MRSA biofilm. Interestingly, DR-AuNPs were also found to promote the lineage commitment of bone marrow-derived mesenchymal stem cells (BMSCs) into osteoblasts in vitro and to enhance their capacity for ectopic bone formation in vivo without causing any cell toxicity.DiscussionOur data provide green DR-AuNPs with dual antibacterial and osteoinductive activities, making them a promising bioactive agent for managing osteomyelitis.